Inclusion complexation of indomethacin with hydroxypropyl-β-cyclodextrin - Jiradej Manosroi (2018)
© 2016, Chiang Mai Journal of Science. All rights reserved. This study aimed to increase the solubility of indomethacin in water by complexation it with hydroxypropyl-β-cyclodextrin (HPβCD). Phase-solubility analysis was used to investigate interactions in aqueous solution between HPβCD and indomethacin. Equimolar indomethacin-HPβCD solid systems were prepared by four different methods including physical mixtures (PM), kneading (KN), coevaporation (COE) and freeze-drying (COL) methods. The complex was characterized by infrared spectroscopy, differential scanning calorimetry, X-ray diffractometry, thin layer chromatography and dissolution rates. The complexation efficiency of indomethacin-HPβCD was determined spectrophotometrically. The solubility of indomethacin increased linearly as the concentration of HPβCD increased. This indicated a feature of the AL-type complex that the water-soluble complexes existed in the solution. The average of apparent 1:1 stability constant of the complex (K1:1) at 30°C was 340 M-1. The KN and COE methods formed partial inclusion complexes, whereas the COL method gave complete complexation. The dissolution rates of indomethacin increased when complexed with HPβCD. HPβCD complexation of an ionized drug molecule by the COL method exhibited the highest dissolution rate of indomethacin [the dissolution efficiency after 90 min (DE90) at 61.7±0.9% and t50% of 13 min., while the uncomplexed indomethacin showed DE90at 15.4±0.1% and t50%more than 90 min. The COL process was the best method because of the high content and dissolution rate of the drug. It is also the simple method to prepare the inclusion complexes. The result from this study has suggested the dissolution rate enhancement of indomethacin by the simple complexaion method with HPβCD.